Antenatal treatment and neonatal outcome of fetal and neonatal alloimmune thrombocytopenia – a 20-years´experience from Norway - Johansen, Tiril (UiT Norges arktiske universitet, 2018)
Introduction: Internationally, recognized anti-HPA-1a-immunized pregnant women are typically treated with high-dose intravenous immunoglobulins (IVIg), although conclusive evidence on IVIg’s efficacy in preventing severe FNAIT is lacking. In Norway, however, IVIg is rarely used. It is therefore relevant to compare FNAIT pregnancy outcome in Norway with other countries where IVIg is more frequently used. The objectives of this study were to assess neonatal outcome (ICH) of FNAIT due to anti-HPA-1a in Norway, and to assess the risk of ICH in subsequent, untreated pregnancies following a history of FNAIT. Materials and method: Data were collected 20 years back in time from time of initiation of the study (1997-2017). Potential patients were identified from the register at the Norwegian National Unit for Platelet Immunology (NNUPI) in Tromsø and from the previous HPA-1 screening study. Antenatal management and neonatal outcome was retrieved from medical records with informed consent. Results: In total, 269 pregnancies from 175 women were included. Antenatal IVIg was given in eight (3 %) of these pregnancies, where none resulted in FNAIT with ICH. Seventeen of the 261 untreated pregnancies were complicated by FNAIT with ICH (6.9 %). Fifteen of ICH cases had no known risk of FNAIT before birth. We identified 7 subsequent, untreated pregnancies where an older sibling had FNAIT with ICH. 2 out of these 7 (29 %) subsequent pregnancies were complicated by ICH in the fetus/neonate. We identified 75 subsequent, untreated pregnancies where a previous child had FNAIT but without ICH. We identified one ICH in this group. The risk of ICH in subsequent, untreated pregnancies was therefore 1.3 %. Conclusion: In the majority of ICH cases the risk of FNAIT was not known before delivery. The risk of ICH in subsequent, untreated pregnancies significantly lower than previously reported by others. By implementing antenatal weekly high dose IVIg treatment to all subsequent pregnancies at risk we would not have prevented any ICH cases ...